2020
DOI: 10.1111/plb.13124
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth‐promoting endophytic bacteria augment growth and salinity tolerance in rice plants

Abstract: • Salt stress negatively affects growth and development of plants. However, it is hypothesized that plant growth-promoting endophytic bacteria can greatly alleviate the adverse effects of salinity and can promote growth and development of plants. In the present research, we aimed to isolate endophytic bacteria from halotolerant plants and evaluate their capacity for promoting crop plant growth. • The bacterial endophytes were isolated from selected plants inhabiting sand dunes at Pohang beach, screened for pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 97 publications
4
51
0
Order By: Relevance
“…This trend of expression level could be attributed to the interaction of MU2 with soybean plants thus, producing hormones and organic acids, which help reduce osmotic stress through the mediation of the antioxidant biosynthetic pathway and osmolytes, activating stress hormones, antioxidant systems, and ion regulating genes leading to salt tolerance, thereby improving salt tolerance in soybean plants. These findings agree with Bharti et al [ 68 ] and Khan et al [ 5 ] who reported the beneficial role of Dietzia natronolimnaea and Arthrobacter woluwensis in mitigating salt stress by demonstrating the expression of various ion transporters and antioxidant-enzymes regulating genes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This trend of expression level could be attributed to the interaction of MU2 with soybean plants thus, producing hormones and organic acids, which help reduce osmotic stress through the mediation of the antioxidant biosynthetic pathway and osmolytes, activating stress hormones, antioxidant systems, and ion regulating genes leading to salt tolerance, thereby improving salt tolerance in soybean plants. These findings agree with Bharti et al [ 68 ] and Khan et al [ 5 ] who reported the beneficial role of Dietzia natronolimnaea and Arthrobacter woluwensis in mitigating salt stress by demonstrating the expression of various ion transporters and antioxidant-enzymes regulating genes.…”
Section: Discussionsupporting
confidence: 92%
“…Higher concentration of soil salinity causes ionic imbalance and leads to osmotic stress, ion toxicity, and mineral imbalance [ 5 ]. Ion toxicity induces the efflux of cytosolic Ca ++ and K + thereby disrupting cellular homeostasis, retarding growth, and causing several physiological and morphological disorders in many crops [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil salinity has been reported to limit crops productivity by impairing the root growth, nutrient uptake and affect metabolic processes [4][5][6]. Salinity stress affect various physiological, morphological and biochemical process which results in reduction of crops biomass and productivity [6,7]. Morphological changes observed under salinity stress on all growth stages including germination, seedling, vegetative and maturity stages [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Various environmental stresses, including drought stress, lead to decreased water availability and osmotic stress that promote the synthesis of endogenous ABA phytohormonal regulation and different antioxidant systems [23,78,79]. It was also observed that alfalfa plants inoculated with AFFR02 and MJ1212 induced drought stress tolerance by reducing water loss (Figure 4A).…”
Section: Discussionmentioning
confidence: 94%